2012
DOI: 10.1155/2012/568312
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Tools for American Cutaneous Leishmaniasis Surveillance and Control: Intervention in an Endemic Area in Rio de Janeiro, RJ, Brazil

Abstract: American cutaneous leishmaniasis (ACL) is a focal disease whose surveillance and control require complex actions. The present study aimed to apply integrated tools related to entomological surveillance, environmental management, and health education practices in an ACL-endemic area in Rio de Janeiro city, RJ, Brazil. The distribution of the disease, the particular characteristics of the localities, and entomological data were used as additional information about ACL determinants. Environmental management actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 19 publications
2
25
0
4
Order By: Relevance
“…Regarding seasonality, previous studies in the Caminho da Cachoeira community (CFMA) reported a higher frequency of L. intermedia in warmer months (January and February) (3) . This result differs partly from the present study, in which the species was captured throughout the year but more frequently in the spring and summer months.…”
Section: Statistical Analysis Of the Collected Datamentioning
confidence: 91%
See 4 more Smart Citations
“…Regarding seasonality, previous studies in the Caminho da Cachoeira community (CFMA) reported a higher frequency of L. intermedia in warmer months (January and February) (3) . This result differs partly from the present study, in which the species was captured throughout the year but more frequently in the spring and summer months.…”
Section: Statistical Analysis Of the Collected Datamentioning
confidence: 91%
“…In the last few decades, ACL has been observed in epidemic outbreaks in different municipalities, including the economically developed City of Rio de Janeiro. In the capital of the state, the disease is particularly prevalent in the western areas (2) of the region around the Pedra Branca massif in the neighborhood of Jacarepaguá where the Campus FIOCRUZ da Mata Atlântica (CFMA) is located (3) .…”
Section: Lutzomyia Longipalpis Lutzomyia Intermediamentioning
confidence: 99%
See 3 more Smart Citations